Taphonomy and Paleoecology of the Bivalve Trace Fossil Protovirgularia in Deltaic Heterolithic Facies of the Miocene Chenque Formation, Patagonia, Argentina - Carmona, Noelia Beatriz (2010)
Lower Miocene tide-influenced deltaic deposits from the Chenque Formation, Patagonia, Argentina, contain abundant and well-preserved biogenic structures attributed to locomotion of deposit-feeder protobranch bivalves. These trace fossils, assigned to the ichnogenus Protovirgularia, consist of delicate, inclined-to-horizontal, chevronate structures, mostly symmetrical with respect to a median axis. Identification of Protovirgularia at sandstone sole beds (hypichnion) is quite straightforward. Endichnial, exichnial and epichnial preservation in heterolithic facies, however, provides a wide variety of forms that depart from the archetypal Protovirgularia and challenges ichnotaxonomic classification. Specimens in prodelta and delta-front facies display morphologic features controlled by substrate fluidity, toponomy, and sedimentation rate. Most specimens show sharp, closely spaced chevrons and occur along sandstone/mudstone interfaces of the proximal prodelta and distal delta-front deposits. These forms reflect how tracemakers experienced significant friction while advancing through the sediment, which resulted in relatively smaller increments of movements. In contrast, variants of Protovirgularia formed in muddier beds, such as in prodeltaic facies, show irregular, poorly defined and unevenly spaced chevrons, and are locally asymmetric in relation to the axis, reflecting softer, water-rich, and plastic substrates. This sediment offered relatively low friction but poor anchorage for the foot. These occurrences of Protovirgularia in tide-influenced, marginal-marine deposits suggests that protobranchs were tolerant of fluctuations in salinity, sedimentation rates, turbidity, and oxygen depletion, displaying opportunistic strategies in stressed nearshore environments. Our evaluation of taphonomic controls and appropriate identification of Protovirgularia can provide valuable information for expanding our knowledge of the ethology and paleoecology of protobranch bivalves.